LOC550643, a Long Non-coding RNA, Acts as Novel Oncogene in Regulating Breast Cancer Growth and Metastasis - Tsai, Kuo-Wang; Chong, Kian-Hwee; Li, Chao-Hsu; Tu, Ya-Ting; Chen, Yi-Ru; Lee, Ming-Cheng; Chan, Shih-Hsuan; Wang, Lu-Hai; Chang, Yao-Jen (Frontiers in Cell and Developmental Biology, 2021)
Metastasis is a major cause of death in patients with breast cancer. Therefore, identifying the molecular mechanisms that regulate metastasis and developing useful therapies are crucial tasks. Long noncoding RNAs (lncRNAs), which are noncoding transcripts with >200 nucleotides, have recently emerged as critical molecules for monitoring cancer progression. This study examined the novel lncRNAs involved in the regulation of cell migration and invasion in breast cancer. This study identified 73 metastasis-related lncRNA candidates from comparison of paired isogenic high and low human metastatic breast cancer cell lines, and their expression levels were verified in clinical tumor samples by using The Cancer Genome Atlas. Among the cell lines, a novel lncRNA, LOC550643, was highly expressed in breast cancer cells. Furthermore, the high expression of LOC550643 was significantly correlated with the poor prognosis of breast cancer patients, especially those with triple-negative breast cancer. Knockdown of LOC550643 inhibited breast cancer cell growth by impairing cell cycle progression. LOC550643 promoted important in vitro metastatic traits such as cell migration and invasion. Furthermore, LOC550643 could inhibit miR-125b-2-3p expression to promote breast cancer cell growth and invasiveness. In addition, by using a xenograft mouse model, we demonstrated that depletion of LOC550643 suppressed the lung metastatic potential of breast cancer cells. Overall, our study shows that LOC550643 plays an important role in breast cancer cell metastasis and growth, and LOC550643 could be a potential diagnosis biomarker and therapeutic target for breast cancer.